Hubungan Self-Esteem dan Body Image pada Remaja Putri di Lembaga Kesejahteraan Sosial Anak (LKSA) - Nurul Aulia Fitra; Sri Putri Rahayu Z; Desmita Desmita; Irman Irman (IAIN Batusangkar, 2021)
The study aims to determine the relationship between self-esteem and body image in adolescent girls in LKSA Kabupaten Lima Puluh Kota. The research method used is the correlation method. The population and sample in this study were 70 young women. Samples were taken using total sampling. Data collection techniques by giving questionnaires, self-esteem and body image questionnaire. The result showed that there was a significant relationship between self-esteem and body image in young woman in LKSA Kabupaten Lima Puluh Kota, with a positive relationship direction. It is known that r hitung is 0,307 > r table 0,235 and with a probability value of sig (0,010 < 0,05). This means that Ho is rejected and Ha is accepted. So, self-esteem has a significant relationship with body image in young women in LKSA Kabupaten Lima Puluh Kota. The higher the self-esteem possessed by young womwn, the higher the body image they have.